Inne miejsca – filmowe obrazy antykwariatu jako heterotopie - Górecka, Ewa (Przestrzenie Teorii, 2019)
Górecka Ewa, Inne miejsca – filmowe obrazy antykwariatu jako heterotopie [Other Places: Cinematic Images of Antiquarian Bookshops as Heterotopias]. „Przestrzenie Teorii” 32. Poznań 2019, Adam Mickiewicz University Press, pp. 197–211. ISSN 1644-6763. DOI 10.14746/pt.2019.32.10. An antiquarian bookshop is a compelling site in the space of culture. Its history and its dense network of associations with an array of other cultural phenomena (e.g. fetishism, collecting, the rise and roles of libraries and museums, to name but a few) have long captivated creative practitioners – writers, painters and film-makers. 84 Charing Cross Road by D.H. Jones, The Ninth Gate by R. Polański and Antykwariat (The Second-Hand Bookstore) by M. Cuske are films in which antiquarian bookshops are appointed similarly central roles, but which at the same time differ from each other generically, each of them being a generic hybrid. In their cinematic renderings, the antiquarian bookshops appear as heterotopias in the sense proposed by Michel Foucault. The representations of the antiquarian bookshop revolve around its otherness vis-à-vis their surroundings, and frame it as unique, functionally variable within culture (a trading venue vs. a meeting point; a trading venue vs. a microcosm) and time-accumulating (heterochrony). Though generically disparate, the cinematic images of the antiquarian bookshop are all intimately embedded in Western culture.